Desenvolvimento e caracterização de hidrogéis eletroativos baseados em poli(metacrilato de 2-hidroxietila) e poli(anilina). - MEDEIROS, Maria Fernanda Xavier Pinto (2017)
A large number of electroactive implantable devices have been developed over the past decades. But the biggest problem of these devices in their application as neural electrode is its relatively low stability, which should lead to the rapid response of the tissue around the implant that causes the device encapsulation after long-term use, limiting the neural communication. The objective of this study was develop electroactive hydrogels based on poly(2-hydroxyethyl methacrylate)(pHEMA) and polyaniline (PANI.CSA) for use as a biocompatible interface between the implantable electrode and the tissue. Firstly, the pHEMAAPS hydrogel was electrosynthesized by cyclic voltammetry and chronopotentiometry in ammonium persulfate solution (APS). A second method used for the preparation of pHEMA was their synthesis on the surface of the platinum electrode (Pt) by chronopotentiometry using as the electrolyte the potassium chloride (KCl), in addition PANI. CSA was electroplated on the surface of pHEMA-electrode system for the preparation of the modified electrode. It then made the electrochemical study by cyclic voltammetry and electrochemical impedance of pHEMA hydrogels, the PANI.CSA and pHEMA/PANI.CSA adhered to the electrode system. The polymerization of pHEMA and PANI.CSA were confirmed by FTIR and UV-Vis which also enabled the identification of the redox states of doped polyaniline with camphor sulfonic acid. For cyclic voltammetry it was also confirmed to electroactive nature of the pHEMA/PANI.CSA system and a porous surface was observed attributed to the presence of the pHEMA in the PANI.CSA matrix. Still it was presented the kinetic study of electroinitiated polymerization of 2-hydroxyethyl methacrylate (HEMA) with electrolysis at constant current using as electrolyte the ammonium persulfate. The formation of the polymer depends on the polymerization time at constant current and the polymerization follows first order kinetics. The molecular weight of the poly (2- hydroxyethyl methacrylate) (pHEMA) in order 105g/mol was obtained by viscometry. Finally, the electroactive hydrogel pHEMAKCl/PANI.CSA presented a fibrillar and porous morphology, conferring good thermal stability and low impedance to the modified electrode Pt-pHEMAKCl/PANI.CSA, suggesting the formation of an interpenetrated polymer network between the hydrogel and the electroactive polymer.